The Association of Oxidative Stress with Parkinson's Disease, a Case-Control Study (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background:Epidemiological studies have proven that some environmental variables, such as exposure to industrially produced materials, usage of agricultural pesticides, or living in a rural area, increase the chance of acquiring Parkinson's disease (PD). It is thought that some environmental pollutants might be the cause of this illness. This was confirmed by the finding that harmful compounds like fungicides like Maneb and herbicides like Paraquat and Diquat selectively act on dopaminergic neurons in the nigrostriatal area of the brain. Recent research has demonstrated that oxidative stress and inflammation are crucial factors in the progression of Parkinson's disease.Materials and Methods:In the present study, 44 blood samples (23 men and 21 women) were obtained from three governorates, namely Najaf Al-Ashraf, Babylon, and Baghdad. Of these, 24 samples (14 men and 10 women) were from Parkinson's disease patients, and 20 samples (9 men and 11 women) were from healthy, uninfected individuals. The serum levels of malondialdehyde, a compound that is a sign of oxidative stress that result from lipid peroxidation, were measured in both in infected and healthy people, and calculating the serum levels of reduced glutathione, which is the master of antioxidants in the body and helps to maintain the balance between oxidants and antioxidants substances.Results:The Statistical results by t-test revealed that there was a significant (P